INTERNET ACCESS RESTRICTIONS IN PAPUA; GOVERNMENT POLICY AND PRESS FREEDOM VIOLATIONS - Dimas Zakaria; Danang Faturrachman Dwicahyo (Faculty of Law Universitas Lampung, 2022)
This research explores how internet access restrictions lead to press freedom violations and how national and international law view restrictions on internet access in the status quo. This research is a normative juridical study analyzed using descriptive-analytical methods, then conveyed using a descriptive-analytical approach to make it easier to conclude. These research findings show that refers to both international law and positive Indonesian law, the government's efforts to prevent the spread of fake news and incitement are correct. Still, the government's policies to restrict internet access in Papua and West Papua are wrong because they have recorded procedures and are against the law. This research concludes that the hate speech that occurred in Surabaya against Papuan students has resulted in riots in Papua and West Papua. In dealing with the spread of fake news and incitement related to this incident, the government has committed violations of press freedom because the Indonesian government's efforts are procedural and contrary to national or international law.